Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Baloch, Faheem Shehzad; Ali, Amjad; Tajibayev, Daniyar; Nadeem, Muhammad Azhar; Ölmez, Fatih; Aktas, Hüsnü; Alsaleh, Ahmad; Cömertpay, Gönül; Imren, Mustafa; Mustafa, Zemran; Dababat, Abdelfattah A.; Yang, Seung Hwan (Springer, 2024)
Puccinia striiformis f. sp. tritici (Pst) is a devastating obligate fungal biotroph that causes stripe rust disease in wheat in temperate and cooler regions, especially in Kazakhstan and Turkey. Chemical control of Pst is not a sustainable or economic strategy in these countries. Therefore, a suitable alternative to these pesticides, such as the development of resistant wheat cultivars, is needed. During the present investigation, a large set of wheat germplasms was characterized to determine the presence of the broad-spectrum resistance Yr15 gene using Y15K1_F2/uhw30_1R primers. This collection contained 360 accessions including 233 durum and bread wheat collected from KASIB cultivars and advanced lines that were developed by eight breeding programs within the Kazakhstan-Siberia Wheat Improvement Network and Turkey, and 127 wild emmer collected from Turkey only. The positive control was wild emmer IDs WEW 83-1, WEW 84-1, and WEW-85, which previously showed positive amplification of the Yr15 gene with these primers. Yr15, a broad-spectrum R-gene derived from wild emmer wheat encoding a putative kinase-pseudokinase protein designated as wheat tandem kinase 1, comprises a unique R-gene structure in wheat against the yellow (stripe) rust. None of the tested cultivated wheat germplasms from 174 durum wheat of the KASIB Network or 59 of bread wheat from Turkey showed positive amplification, but 89 of 127 (70.07%) wild Triticum dicoccoides showed positive amplification. The collection from the Karacadağ regions showed the maximum number of genotypes (46) with positive amplification for Yr15, followed by Eruh (10), Şırnak (5), Malazgir-Tunceli (4), Tunceli (4), Şırnak-Uludere yol (3), Tunceli-Pülümür (3), and Karacadağ/Kerteş Köyü –Siverek (3). We conclude that wild wheat cultivars are a good source of the Yr15 gene and that introgression of this gene into the cultivated wheat germplasm of both countries should be performed to manage the Pst pathogen in the future.